Development Model on Prevention of Land and Forest Fire in the Peat Land Area with Empowerment Society Approach (Case Study in West Kalimantan) - Maswadi; Oktoriana, Shenny; Hazriani, Rini; Maulidi (Talenta Publisher, 2020)
Land fires are an annual agenda in Indonesia, especially in areas covered by peatlands. Peatland management using fire is the main cause. The general paradigm for land fires is that the farmers' economy is low. In fact, the factors that cause land fires are not only from the economic aspect, but from the social and institutional aspects which affect the behavior of farmers. Therefore, the purpose of this study is (1) to analyze the correlation of factors that influence land burning behavior, and (2) to determine the model for the changing of burning behavior into non burning farm land cultivation, in order to prevent land fire in Kuburaya Disrict and Bengkayang District, West Kalimantan. The research involved farmers farming on peatlands in both districts. Regression models was used for the correlation analysis. Based on the results of the regression analysis, a land burning behavior change model was determined based on the influencing factors descriptively. The result of the analysis showed the factors that significantly influence land burning behavior at the household level are knowledge level (consist of farming problems faced by farmers, agricultural extension materials and the application of technology), observance of rules, activeness of mutual assistance, cosmopolitan level, appraisal on burning behavior, and imitation level. The resulting model for changing the behavior of burning land is implementing activity of assistance, social capital stimulus and positive agreements/ pressure to the land users.